Global Domestic Workers - Marchetti, Sabrina (Bristol University Press, 2021)
"EPDF and EPUB available Open Access under CC-BY-NC licence. Drawing from the EU-funded DomEQUAL research project across nine countries in Europe, South America and Asia, this comparative study explores the conditions of domestic workers around the world and the campaigns they are conducting to improve their labour rights. The book showcases how domestic workers' movements put 'intersectionality in action' in repre-senting the interest of various marginalized social groups from migrants and low-income groups to racialized and rural girls and women. This will be an invaluable for scholars, policy makers and activists alike."